Does the Covid-19 Pandemic Affect the Travel Intentions of Comorbid Individuals ? - Riko Erlima Putra; Verinita Verinita; Eri Besra (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of health risk tendencies and the focus of prevention on travel intentions on the history of comorbid individuals in the city of Padang during the COVID-19 pandemic with xenophobia as a moderating variable. The sample of this study was all comorbid individuals in the city of Padang using purposive sampling technique. The research data processing was carried out using the SmartPLS3 test tool. The results showed that health risk propensity had a positive and significant effect on travel intentions, the focus of prevention had no significant effect on travel intentions. Xenophobia as a moderating effect with a tendency to health risks and a focus on prevention also did not significantly affect the intention to travel.